Social Representations of the Marriage Partner: a Generational Approach - Emelyanova T.P.; Shmidt D.A. (Социальная психология и общество, 2021)
Objective. Comparison of the marriage partner social representations of representatives of generations Y, X and Baby Boomers. Background. The sphere of marriage and romantic relationships is influenced by transformational processes in society. The romanticization of loneliness, the postponement of marriages and the births causes the interest in the study of social representations about the marriage partner of post-student youth. Study design. The article examines the possible connection between social representations of a marriage partner and the family role positioning on the one hand, and the content about romantic relationships that respondents browse in social networks, on the other. The Kraskal-Wallace H criterion was used to check existence and sort of possible connection. Participants. Sample: 525 people, including Millennials — 192 people, representatives of generation X — 176 and baby boomers — 157. Measurements. Author’s questionnaire of social representations about marriage and marriage partner; questionnaire “Marriage Role Expectations and Claims” by A. Volkova; set of questions about usage of social networks and other communication channels. Results. The core of social representations about the marriage partner and the periphery close to the core change slightly from generation to generation. With the growth of respondents’ life experience increases the willingness to accept complex life circumstances and the perception of relationship as a process that requires permanent effort. Conclusions. Problematic trends in family and marriage relations are presumably the result of sociocultural changes, rather than social representations of the marriage partner.